Case report: Total enterectomy following complete small bowel ischaemia in the post-peritonectomy setting. (2020) - Coulshed, A.; Soucisse, M.; Lansom, J.D.; Morris, D.
Highlights: Small bowel resection following total ischaemia is feasible post-peritonectomy. VAC dressing and skin grafting was beneficial following wound dehiscence. Small bowel transplant is a potential means to avoid complications of long-term TPN. Abstract: Introduction: This report presents the rare case of a patient with complete bowel ischaemia following parastomal hernia, leading to total bowel resection, with consideration of post-operative complications and wound management. Presentation of case: A 59 year old female was found to have complete small bowel ischaemia on exploratory laparatomy, on a background of recurrent appendiceal adenomucinosis, for which she had received previous peritonectomy, cholecystectomy, total colectomy, and partial small bowel resection. The patient was managed with total enterectomy and post-operative total parenteral nutrition. Discussion: Total enterectomy represents a significant challenge in the postperitonectomy setting, including consideration of wound management with the empty abdomen, and the potential of small bowel transplant in management. Conclusion: Resection of the small bowel following total small bowel ischaemia is feasible in the post-peritonectomy setting, given appropriate post-operative care and wound management. However, long-term survival remains challenging, especially without small bowel transplant.